Effect of biomechanical disturbance of the temporomandibular joint on the prevalence of internal derangement in mandibular asymmetry - B. Buranastidporn (2018)
The aim of the present study was to elucidate the relationship between biomechanical changes of the temporomandibular joint (TMJ) and internal derangement (ID) symptoms in mandibular asymmetry. Posteroanterior cephalograms (PA) of 140 patients with TMJ ID associated with mandibular asymmetry were used to investigate the inclination of the frontal occlusal plane (FOP), and were analysed in conjunction with the results of a report providing information on ID symptoms. A three-dimensional (3D) finite element model (FEM) of the entire mandible was created to investigate the distribution of TMJ forces during clenching. The inclination of the FOP was modified to simulate various degrees of vertical asymmetry. The stresses on the TMJ on the ipsilateral and contralateral sides were analysed and their values were compared with those of the standard model. The results showed that the symptomatic sides were significantly related to the degree of inclination of the FOP. Increasing its angulation resulted in a decrease of the symptoms on the ipsilateral side and an increase of those on the contralateral side. The analysis showed that stress-distribution patterns and overall stresses of the articular disc were influenced by the angulation of inclination of the FOP. These mechanical changes exhibited a distinct relationship with the prevalence of ID in the patients. These results suggest that disturbances in the stresses either in amount or direction due to occlusal inclination can be responsible for ID. Therefore, an attempt to establish a flat occlusal plane is an important orthodontic treatment objective in maintaining the normal health and structure of the TMJ. © The Author 2005. Published by Oxford University Press on behalf of the European Orthodontics Society. All rights reserved.